A New Mechanistic Model for Viral Cross Protection and Superinfection Exclusion - Zhang, Xiao-Feng; Zhang, Shaoyan; Guo, Qin; Sun, Rong; Wei, Taiyun; Qu, Feng (Frontiers in Plant Science, 2018)
Plants pre-infected with a mild variant of a virus frequently become protected against more severe variants of the same virus through the cross protection phenomenon first discovered in 1929. Despite its widespread use in managing important plant virus diseases, the mechanism of cross protection remains poorly understood. Recent investigations in our labs, by analyzing the whole-plant dynamics of a turnip crinkle virus (TCV) population, coupled with cell biological interrogation of individual TCV variants, revealed possible novel mechanisms for cross protection and the closely related process of superinfection exclusion (SIE). Our new mechanistic model postulates that, for RNA viruses like TCV, SIE manifests a viral function that denies progeny viruses the chance of re-replicating their genomes in the cells of their “parents”, and it collaterally targets highly homologous superinfecting viruses that are indistinguishable from progeny viruses. We further propose that SIE may be evolutionarily selected to maintain an optimal error frequency in progeny genomes. Although primarily based on observations made with TCV, this new model could be broadly applicable to other viruses as it provides a molecular basis for maintaining virus genome fidelity in the face of the error-prone nature of virus replication process.